FEATURES OF THE DEBUT OF ACUTE MYOCARDITIS IN PATIENTS AFTER COVID-19 INFECTION - Kovalenko, V.M.; Nesukay, E.G.; Talaieva, T.V.; Sychov, O.S.; Cherniuk, S.V.; Kirichenko, R.M.; Tretiak, I.V. (World of Medicine and Biology, 2023)
The purpose of the study was to perform a comparative assessment and analysis of the relationship between parameters of immune status and the structural and functional state of the heart in patients with acute myocarditis who had or did not have a history of COVID-19 infection. According to the results of the study, patients with acute myocarditis and a history of COVID-19 infection were characterized by a larger volume of inflammatory and fibrotic damage to the myocardium and more pronounced violations of the contractility of the left ventricle compared to patients who did not have a history of coronavirus infection. In addition, patients with myocarditis and previous coronavirus infection were characterized by a more pronounced activation of immunopathological reactions, which was accompanied by a higher level of C-reactive protein, pro-inflammatory interleukin-6, ferritin and troponin I as a marker of cardiomyocyte damage. The use of factor analysis made it possible to establish the limit values of instrumental and laboratory indicators associated with the presence of widespread inflammatory/fibrotic lesions of the left ventricle in patients with acute myocarditis and history of COVID-19: the values of left ventricle longitudinal, global systolic strain of the ≤9.0 % and the left ventricle end-diastolic volume index ≥95 ml/m2, as well as the content of tumor necrosis factor-α ≥7.5 pg/mL and C-reactive protein ≥12.0 mcg/ml in blood serum.
Keywords: acute myocarditis; coronavirus infection; immunopathological reactions; left ventricle global systolic strain; inflammatory and fibrotic changes in the heart